2006
DOI: 10.1111/j.1467-8268.2006.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Development and Economic Growth: Evidence from Cote D'Ivoire

Abstract: The present paper investigates the relationship between the development of the Ivorian stock market and the country's economic performance. Stock market development indicators were identified and used to calculate the Ivorian stock market development index. A set of control variables were also identified. The empirical results suggest that gross domestic product and stock market development are cointegrated when the control variables are included in the analysis. That is, there is a long-run relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…However, this was attributed to low level of income as evidenced in most developing countries. Similar result was obtained by Nzue (2006) who investigated the relationship between the development of the Ivorian stock market and the country's economic performance. His findings suggest that gross domestic product and stock market development were co-integrated when the control variables were included in the analysis.…”
Section: Literature Surveysupporting
confidence: 83%
See 1 more Smart Citation
“…However, this was attributed to low level of income as evidenced in most developing countries. Similar result was obtained by Nzue (2006) who investigated the relationship between the development of the Ivorian stock market and the country's economic performance. His findings suggest that gross domestic product and stock market development were co-integrated when the control variables were included in the analysis.…”
Section: Literature Surveysupporting
confidence: 83%
“…The high ratio of banking sector credit toGDP suggests that availability of finance is not the problem, rather, the inefficient and low productivity of investment in the private sector. On the contrary, the studies for Ghana, Ivory Coast and India by Osei (2005), Nzue (2006) and Mishra, Das and Pradhan (2009), where investment productivity is high, reveal that credit market development enhanced economic development in the respective economies.…”
Section: Introductionmentioning
confidence: 99%
“…1 The incorporation of a control variable equally helps to make our analysis multivariate as against bivariate. This is important because some studies have shown that two variables might not be cointegrated under bivariate analysis but cointegrated when control variables are included (see the work of Nzue, 2006). 2 We measured pro…tability as return on total assets.…”
Section: Model Specification and Datamentioning
confidence: 99%
“…3 Most existing studies have adopted either simple OLS regression (Levine & Zervos, 1993); Instrumental variables procedure (Beck et al, 2000); difference panel estimator (Rousseau & Wachtel, 2000); Generalized method of moment technique (Beck & Levine, 2002). Some have equally used cointegration and error correction approach (Arestis et al, 2001;N'zue, 2006;Rousseau & Sylla, 2005). high economic growth creates demand for certain financial instruments and arrangements and that financial markets effectively respond to these demands and changes.…”
Section: Theoretical Issuesmentioning
confidence: 99%